Transfer of Maternal Immune Cells by Breastfeeding: Maternal Cytotoxic T Lymphocytes Present in Breast Milk Localize in the Peyer's Patches of the Nursed Infant. - Allison Cabinian; Daniel Sinsimer; May Tang; Osvaldo Zumba; Hetali Mehta; Annmarie Toma; Derek Sant'Angelo; Yasmina Laouar; Amale Laouar (PLoS ONE, 2016)
Despite our knowledge of the protective role of antibodies passed to infants through breast milk, our understanding of immunity transfer via maternal leukocytes is still limited. To emulate the immunological interface between the mother and her infant while breast-feeding, we used murine pups fostered after birth onto MHC-matched and MHC-mismatched dams. Overall, data revealed that: 1) Survival of breast milk leukocytes in suckling infants is possible, but not significant after the foster-nursing ceases; 2) Most breast milk lymphocytes establish themselves in specific areas of the intestine termed Peyer's patches (PPs); 3) While most leukocytes in the milk bolus were myeloid cells, the majority of breast milk leukocytes localized to PPs were T lymphocytes, and cytotoxic T cells (CTLs) in particular; 4) These CTLs exhibit high levels of the gut-homing molecules α4β7 and CCR9, but a reduced expression of the systemic homing marker CD62L; 5) Under the same activation conditions, transferred CD8 T cells through breast milk have a superior capacity to produce potent cytolytic and inflammatory mediators when compared to those generated by the breastfed infant. It is therefore possible that maternal CTLs found in breast milk are directed to the PPs to compensate for the immature adaptive immune system of the infant in order to protect it against constant oral infectious risks during the postnatal phase.